The Effectiveness of the Shadowing Method on the Hatsuon Ability of UMY PBJ Study Program Students Class of 2023 - Wahyuni, Yuli; Abdinegara, Hansel Mahesa (Jurnal Bahasa Jepang Taiyou, 2024)
Appropriate methods are needed to support Japanese pronunciation skills (Hatsuon). This research uses the Shadowing method so that Japanese language learners get used to listening to how Japanese people speak and understand how to pronounce Japanese vocabulary correctly. Researchers researched UMY PBJ study program students in the Class of 2023 because their Japanese pronunciation skills still needed to be improved. Apart from that, the 2023 UMY PBJ study program students, in this case, are first-year students who have never received Japanese language pronunciation learning or training. Therefore, it is hoped that conducting this research will help UMY PBJ study program students, Class of 2023, to master Japanese pronunciation better. This research aims to determine the effectiveness of the Shadowing method in the scope of long vowel sounds (Choo on), nasal sounds (Hatsu on), and double consonant sounds (Soku on), as well as the response of learners to the application of the shadowing method in learning language pronunciation. Japan. This research uses an experimental method with a one-group pretest-posttest approach. The sample of this research was 12 students of the Japanese Language Education Study Program, Yogyakarta Muhammadiyah University Class of 2023, who were taken at random or random sampling. The results of the calculation state that the shadowing method effectively improves Hatsuon's abilities. Apart from that, the results of the questionnaire analysis show that almost all students think the shadowing method helps improve hatsuon abilities